IMPACT OF OBESITY, DIABETES, AND SMOKING ON SPINE SURGERY OUTCOMES (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize contemporary evidence on how obesity, diabetes mellitus, and smoking influence perioperative and longer‑term outcomes after spine surgery, and to highlight practical optimization strategies.Methods: A narrative review of recent systematic reviews, meta‑analyses, guidelines and large cohort studies published mainly from 2016-2025 was conducted via PubMed and major spine journals. Key outcomes included surgical site infection, pulmonary and renal complications, pseudarthrosis/nonunion, reoperation, length of stay, and patient‑reported outcomes.Results: Obesity is associated with higher nonunion rates and worse patient‑reported outcomes following lumbar fusion, with increased perioperative events in many - but not all - procedures. Diabetes confers higher risks of surgical site infection and medical complications after fusion and other spine procedures; elevated preoperative HbA1c (7.5-8.0%) correlates with higher infection risk and poorer recovery. Smoking robustly increases pseudarthrosis and adverse outcomes after fusion; preoperative smoking cessation of at least four weeks reduces infectious, wound, and pulmonary complications. Enhanced recovery after surgery pathways support risk factor optimization and have demonstrated benefits in spine care.Conclusions: Obesity, diabetes, and smoking adversely affect spine surgery outcomes, especially fusion biology and infection risk. Prehabilitation bundles incorporating weight management, glycemic optimization (target HbA1c ≤ 7.5% when feasible), and verified smoking cessation ≥ 4 weeks should be prioritized to improve outcomes.
Keywords: Spine surgery, obesity, diabetes mellitus, smoking, fusion, complications.